Association Between Thyroid Hormones, Thyroid Antibodies, and Cardiometabolic Factors in Non-Obese Individuals With Normal Thyroid Function - Liu, Jia; Duan, Yan; Fu, Jing; Wang, Guang (Frontiers in Endocrinology, 2018)
Background: Hypothyroidism is an important risk factor for cardiovascular diseases, and autoimmune thyroiditis (AIT) is the leading cause of hypothyroidism. Recent studies showed that even AIT patients with euthyroidism still had an increased number of early atherosclerotic lesions. However, the precise mechanism is not yet known. This study aimed to investigate the association of thyroid function, thyroid autoimmunity and cardiometabolic risk factors in non-obese AIT patients with euthyroidism. Methods: A total of 5,608 non-obese individuals including 1,402 AIT patient and 4,206 sex-, age- and BMI- matched healthy controls were recruited. Results: The AIT patients had significantly lower FT3 and FT4 levels, and higher TSH, TPOAb and TgAb levels. The elevated levels of hsCRP and HOMA-IR were observed in the AIT patients than the controls [hsCRP: 0.65 (0.27 – 1.33) vs. 0.20 (0.03 – 0.74) mg/L; HOMA-IR: 2.78 ± 1.60 vs. 2.33 ± 1.49; all P < 0.05]. Thyroid function was not associated with metabolic parameters and inflammatory makers, while the TPOAb titer was positively associated with the HOMA-IR and hsCRP levels after adjustment for confounding factors (all P ＜0.05). Multivariate regression analysis demonstrated that the TPOAb level was an independent influencing factor for the HOMA-IR and hsCRP levels (HOMA-IR: β = 0.058, P < 0.05; hsCRP: β = 0.108, P < 0.05). Conclusions: The TPOAb level is associated with HOMA-IR and hsCRP levels independently of thyroid function in non-obese individuals. Mild deviation of thyroid function within the normal range, chronic inflammation, and insulin resistance may be the links between AIT and atherosclerosis in the non-obese population.